Analisis Pelaksanaan Pertukaran Informasi Otomatis Perpajakan Dari Perspektif Efektifitasnya Meminimalkan Tax Evasion Pada Direktorat Jenderal Pajak Tahun 2018-2020 - Sari Narulita; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2023)
This research aims to analyze the implementation of automatic tax information exchange from the perspective of its effectiveness in minimizing tax evasion at the Directorate General of Taxes in 2018-2020 and to analyze the inhibiting and encouraging entities in the automatic exchange of information in minimizing tax avoidance at the 2018-2020 DGT. The author uses a qualitative method with a descriptive approach. Data collection techniques used in the form of interviews, observation, documentation, and triangulation of sources. The results of the study conclude that the Implementation of Automatic Information Exchange (AEoI) in minimizing tax avoidance and tax evasion so far has been quite effective according to international standards, although there are still many complete data sets that have not been met by partner countries such as Singapore, resulting in the data provided by the partner country being incomplete. can be used by the Indonesian tax authorities. However, the performance of AEoI has not provided optimal results in increasing tax revenue, especially in 2020, its progress is hampered by the Covid 19 Pandemic. On the other hand, the Directorate General of Taxes is still experiencing obstacles. There are four obstacles and challenges in the AEOI, namely: First, the Reciprocity of Information Exchange (Reciprocity). Second, banking tends to be resistant to data access. Third, the lack of technology that supports AEoI. Fourth, the complexity of Conversion of Tax Revenue Data. The Entity that drives this information exchange in minimizing tax avoidance is the existence of an Information Exchange System called the “Common Transmission System (CTS)”.